University Student Attitudes Toward Persons With a History of Adult Sexual Violence and Their Correlates With Policy, Treatment, and Management - Corăbian, Gabriela (Journal of interpersonal violence, 2023)
Empirical evidence suggests that postsecondary students are disproportionately impacted by sexual violence. Further evidence suggests that most persons convicted of crimes involving sexual violence return to the community, and that social factors, including public policy and community members’ attitudes and perceptions, are key determinants of successful reintegration among these persons. Taken together, these observations suggest that students’ perspectives should be considered in discourse related to reintegration. The current study aimed to assess the attitudes of a university undergraduate sample toward men convicted of adult sexual violence as well as their level of support for various community-based policies to manage this population upon release from custody. Participants (N = 333) completed a survey battery comprising measures of three dimensions of attitudes toward persons who have sexually offended, perceptions of recidivism and treatment response, and support for various incapacitation/control (IC) and rehabilitative/reintegration (RR)-based policies. Results varied depending on the dimension of attitudes measured, with the affective component appearing to be the most markedly negative. Participants endorsed a mixture of IC and RR policies, with attitudinal measures predicting policy endorsement controlling for relevant demographic variables. The results provide a framework for future research surveying a more representative sample of the Canadian public, while also providing useful information for policymakers relying on community support to reduce sexual offending.